Cognitive approaches to Old English poetry - Harbus, Antonina, 1968- (Anglo-Saxon studies, 2012)
"A major, thoughtful study, applying new and serious interpretative and critical perspectives to a central range of Old English poetry." Professor John Hines, Cardiff University. Cognitive approaches to literature offer new and exciting ways of interpreting literature and mentalities, by bringing ideas and methodologies from Cognitive Science into the analysis of literature and culture. While these approaches are of particular value in relation to understanding the texts of remote societies, they have to date made very little impact on Anglo-Saxon Studies.